ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI WAJIB PAJAK DALAM PENGURUSAN RESTITUSI PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA BENGKULU - Triansyah, Hapizar; Susena, Karona Cahya (Ekombis Review, 2014)
Hapizar Triansyah, Karona Cahya Susena; The purpose of this research is to determine the Factors Affecting What Are The Dominant taxpayer Handling Tax Refund Kantor Pelayanan Pajak Pratama bengkulu. analysis results can be used as consideration Bengkulu Pratama Tax Office to improve the management of restitution in the future. Type of research is descriptive qualitative. researchers also conducted a descriptive analysis of the dominant factors that affect taxpayers in obtaining refunds of taxes. in this study also uses data analysis to reating scale raw data is numeric then interpreted in a qualitative sense, so measurements using this scale reating change in processing quantitative data into kaulitatif.Produce research results that of the five indicators of the number of respondents expressed a statement about obtaining tax refunds with a score of 165.1 is in the interval 146-179 that are in the area of effect. It is stated that the five indicators in the management of tax refunds for taxpayers affected. Processing of tax refunds that participate filled out a questionnaire in general expressed a very good response . Continuum corresponding graphs we know that the statement is the dominant procedure with a score of 188.6 Restitution is in the interval 180-213 which was very influential in the area of the highest ranks.Â Key words:Sanctions,Period of Restitution, Restitution Procedures, Tax Audit,Tax Officer